Pengaruh Model Pembelajaran Kooperatif Tipe Team Games Tournament Terhadap Hasil Belajar pada Mata Pelajaran IPA di Kelas IV SDIT Ummu Hafidzah Sibiru-Biru - Ekawati, Sri; Harahap, Syarifah Ainun; Ramadhan, Nuri (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2024)
This study examines the effect of the cooperative learning model, specifically the Talking Stick type, on student independence in fourth-grade students at SDIT Ummu Hafidzah Sibiru-Biru. The research utilized a quasi-experimental design with a control and experimental group. The results indicate that Prototype Learning falls within the good category, as does student independence, with the experimental class achieving an average score of 82.2. In contrast, students who did not use Prototype Learning obtained an average score of 51.67. The standard deviation values were 9.06 for the experimental group and 7.18 for the control group. Hypothesis testing revealed a calculated t-value (th) of 0.06, which was compared to the t-table value of 0.245 at a 5% significance level with N = 60. Since 0.245 > 0.06, the hypothesis was accepted, confirming the significant effect of the cooperative Talking Stick learning model on student independence. These findings suggest that implementing cooperative learning strategies can enhance student autonomy in primary education settings.